2015
DOI: 10.1377/hlthaff.2015.0667
|View full text |Cite|
|
Sign up to set email alerts
|

Diet And Perceptions Change With Supermarket Introduction In A Food Desert, But Not Because Of Supermarket Use

Abstract: Placing full-service supermarkets in food deserts (areas with limited access to healthy foods) has been proposed as an important policy strategy to confront inequalities in healthy food access. Capitalizing on a natural experiment, we enrolled n=1,372 randomly selected households from two comparable neighborhoods, one of which received a full-service supermarket in 2013. We looked at the impact on residents’ diet, perceived access to healthy foods and satisfaction with one’s neighborhood as a place to live. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
246
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(254 citation statements)
references
References 29 publications
7
246
0
1
Order By: Relevance
“…Other solutions may require the collaboration of business, government, and community groups. In the case of "food deserts" (locations in underprivileged areas devoid of fresh food retailers), new research has shown that the introduction of new stores promotes little change in entrenched eating habits (Dubowitz et al 2015). Instead, social marketing programs to prompt new food purchasing behaviors must also be implemented.…”
Section: Stakeholdersmentioning
confidence: 99%
“…Other solutions may require the collaboration of business, government, and community groups. In the case of "food deserts" (locations in underprivileged areas devoid of fresh food retailers), new research has shown that the introduction of new stores promotes little change in entrenched eating habits (Dubowitz et al 2015). Instead, social marketing programs to prompt new food purchasing behaviors must also be implemented.…”
Section: Stakeholdersmentioning
confidence: 99%
“…44 A similar study in Pittsburgh (PA) also found changes in perceptions, but an improvement in diet quality could not be attributed to shopping at the new supermarket. 45 …”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…For example, policymakers have proposed building new supermarkets in so-called "food deserts" -low-income neighborhoods with poor geographic access to supermarkets -based on a large body of cross-sectional research identifying a link between closer proximity to supermarkets and positive health and diet outcomes. 24 However, the few longitudinal studies that have looked at causality have found no relationship between new neighborhood supermarkets and weight outcomes; [43][44][45] although one study did see higher dietary quality after the supermarket opened, this could not be attributed to use of the supermarket. 45 It's still not clear whether adding supermarkets will result in improving health and it's quite possible that supermarkets could make outcomes worse.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Of studies finding improvements in healthy purchasing, these changes are not attributable to the use of the new retailer. 9,10 Evaluations also highlight the importance of in-store environment, including pricing, placement, and promotions, in motivating behavior change, 6,11 although none have explored shoppers' in-store experiences.…”
Section: Introductionmentioning
confidence: 99%